Integration of Madrasah Curriculum Management with Pesantren Curriculum to Enhance Religious Moderation at Pondok Pesantren Darul Musthofa NW West Lombok - Jayadi, Taupan; Maujud, Fathul; Thohri, Muhammad (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study investigates the integration of madrasah and pesantren curricula to enhance religious moderation at Pondok Pesantren Darul Musthofa NW West Lombok. The research aims to assess how curriculum integration can foster religious moderation among students. Employing a qualitative approach, the study uses interviews with pesantren leaders, observations, and document analysis to gather primary and secondary data. Data analysis includes collection, presentation, reduction, and conclusion drawing, validated through source, method, and time triangulation. The findings indicate that integrated curriculum planning at Darul Musthofa NW encompasses several key processes: First, Needs Analysis, addressing institutional needs (vision, mission, human resources, and learning resources), teacher needs, and student needs; Second, Educational Goals, focusing on developing students with strong faith, scientific knowledge, and moral values, while promoting a respectful and tolerant learning environment; Third, Curriculum Flexibility, adapting to societal knowledge needs within the pesantren context; and Fourth, Teacher Collaboration, involving inter-subject cooperation, routine meetings, joint training, and professional development. The implementation includes: First, madrasah-level curriculum preparation and extracurricular activities; Second, class-level curriculum emphasizing religious moderation in Islamic subjects; and Third, teaching methods such as classical-khalaqah, mudzakarah, memorization, and Qiroati. Evaluation methods use the EKOP model for assessing students and teachers, with additional assessments through national exams and pesantren tests. This integration enhances students' religious moderation and provides a comprehensive educational framework.